An Analysis of Student Learning Barriers for Elementary School Students in Understanding Mathematical Concepts of Fractions - Meilani Rohmelia Dewi; Jumadi; Wahyudi (Jurnal Pendidikan Matematika (JPM), 2024)
This study aims to: (1) describe the achievement of indicators for understanding students' mathematical concepts about fractions. (2) Describe the learning barriers that occur in students and the factors that cause them to understand the mathematical concept of fractions. This research is a qualitative descriptive study conducted in class IV MI Darul Muttaqin Sukomangu, with a total of 10 students. All students are given a test to measure the achievement of indicators of understanding the concept. The test results are then grouped into 3 categories, namely high, medium, and low. From each category, interview subjects were selected with the criteria of not achieving some or all of the indicators of understanding the concept and having good communication skills. This interview aims to determine the learning barriers that occur and the factors that cause them. The data analysis technique was carried out in three stages, namely data condensation, data presentation, and conclusion. The test results show that 4 students fall into the category of high concept understanding, 3 students in the medium category, and 3 students in the low category. In the results of the interview, it was found that there were learning barriers, namely ontogeny and epistemological barriers. The most dominant obstacle is the ontogeny barrier with indicators of lack of concentration when learning begins. In addition, the most dominant factor was found, namely internal factors in the form of emotional aspects or wrong attitudes, namely lack of learning.